Production and purification of bacteriocin-like inhibitory substance from Pediococcus acidilactici Kp10 - Md Sidek, Nurul Lyana (2016)
Recent interest in biopreservatives as natural substitute has grown among consumer for its ability to maintain the organoleptic, nutritional properties and safety of the food with little usage of chemical preservatives and lower heat intensity. Several bacteriocin-like inhibitory substance (BLIS) have been produced from the two principal species of Pediococcus, Pediococcus acidilactici and Pediococcus pentosaceus.The major problem regarding the application of bacteriocin-producing starter culture and BLIS in food fermentation is to determine the suitable condition that can promote both growth and BLIS production as well as simple and low cost purification method. The characteristics of BLIS also determine the effectiveness of their incorporation into the food products. In this study, the ability of P. acidilactici Kp10 strain in producing bacteriocin-like inhibitory substance (BLIS) in various medium formulations was investigated by shake flask fermentations at condition of 28.5˚C, 120rpm for 24h. M17 (3822.95 AU/mL) was chosen as the best media among MRS, TSB, and NB according to its high bacterial cell growth and BLIS production. A one-way between groups analysis of variance (ANOVA) was used to investigate the ability to produce high BLIS production among those four basal media. The ANOVA was statistically significant (p<0.05), indicating that M17 produce highest BLIS production. However, MRS, TSB and NB media did not significantly differ with each other (p > 0.05) upon Post-hoc comparison using the Tukey HSD test. The stability of crude extract of BLIS produced by P. acidilactici Kp10 has also been evaluated under different temperatures, pHs and storage periods with different indicator microorganisms (L. monocytogenes ATCC 15313, E. coli ATCC 35218 and S. aureus ATCC 33591).The results represented robust characteristics of BLIS at wider pH range (pH2-9), temperature (4˚C, -20˚C, -80˚C, 100˚C, and 121˚C) and long period of storage (1, 3, and 6 months) at 4˚C, -20˚C, and -80˚C temperature. The purification of crude extract of BLIS was conducted using aqueous two-phase flotation system (ATPF) with polyethylene glycol (PEG) and sodium citrate.The optimum purification condition of BLIS by ATPF was achieved at PEG 8,000/sodium citrate comprising TLL of 42.6, VR of 0.4, CL of 22% (w/w) at pH 7 with an average Ft of 30 min and FR at 20 mL/min. BLIS of P. acidilactici Kp10was successfully purified using aqueous two-phase flotation system (ATPF) which gave the purification of 5.9-fold with a separation efficiency of 99%.The size of purified BLIS from SDSPAGE analysis is 12.5 kDa. The findings revealed a great potential for commercial application of BLIS from P. acidilactici Kp10 strain.